Wave-canceling acoustic metarod architected with single material building blocks - Ogasawara, Akira; Fujita, Kentaro; Tomoda, Motonobu; Matsuda, Osamu; Wright, Oliver B. (Applied physics letters, 2020)
Preventing elastic waves from traveling down thin structures is a subject of great interest from the point of view of both physics and applications. It represents a problem—mirrored by the case of light in waveguides—that has broad implications. To completely prohibit sound waves in a given frequency range in rods, for example, all axially propagating acoustic eigenmodes must exhibit strong damping. Here, we demonstrate experimentally and by simulation a metamaterial rod made from a single material that can simultaneously shut out all elastic-wave polarizations, namely longitudinal, flexural, and torsional modes, in a band in the sub-kHz range. We first bond five acrylic building blocks together to make a subwavelength resonator and then fix an array of these inside an acrylic tube to form a cylindrical metarod that inhibits sound transmission in the metamaterial bandgap frequency range. Applications include vibration control and earthquake mitigation.